2021
DOI: 10.1021/acschemneuro.1c00006
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of α-Synuclein Binding to Lipid Membranes

Abstract: Cooperative binding is a key feature of metabolic pathways, signaling, and transport processes. It provides tight regulation over a narrow concentration interval of a ligand, thus enabling switching to be triggered by small concentration variations. The data presented in this work reveal strong positive cooperativity of α-synuclein binding to phospholipid membranes. Fluorescence cross-correlation spectroscopy, confocal microscopy, and cryo -TEM results show that in excess of vesicles α-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…In all of the protein-containing samples, α-synuclein was added to attain a lipid-to-protein (L/P) ratio of 200. We have previously shown that for the DOPC:DOPS 7:3 system at this L/P virtually all α-synuclein molecules are bound to the membrane Makasewicz et al (2021). We note that there are a few examples of deformed vesicles present in the sample containing only vesicles in MES buffer (Figure 1A,C), which can be explained by that some amount of water may evaporate from the thin liquid 100 film during cryo-TEM sample deposition.…”
Section: α-Synuclein Induces Deformation Of Small Unilamellar Vesiclesmentioning
confidence: 69%
“…In all of the protein-containing samples, α-synuclein was added to attain a lipid-to-protein (L/P) ratio of 200. We have previously shown that for the DOPC:DOPS 7:3 system at this L/P virtually all α-synuclein molecules are bound to the membrane Makasewicz et al (2021). We note that there are a few examples of deformed vesicles present in the sample containing only vesicles in MES buffer (Figure 1A,C), which can be explained by that some amount of water may evaporate from the thin liquid 100 film during cryo-TEM sample deposition.…”
Section: α-Synuclein Induces Deformation Of Small Unilamellar Vesiclesmentioning
confidence: 69%
“…Here, the lipid-to-protein ratio, L/P = 5, is relatively low, and we expect to have a significant fraction of free, nonadsorbed aSyn molecules. 17 The excess of the free protein allows for the fibril formation to take place, as discussed in Galvagnion et al 23 …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that monomeric αS adsorbs to anionic lipid membranes (Jao et al, 2004;Pfefferkorn et al, 2012;Hellstrand et al, 2013a;Fusco et al, 2014), and that the membrane under some conditions can have a catalytic effect on fibril formation (Galvagnion et al, 2015;Grey et al, 2015;Galvagnion, 2017;Gaspar et al, 2019). Interestingly, this adsorption appears to be a strongly cooperative process (Makasewicz et al, 2021). Several studies, performed with different systems, have also indicated that αS and lipids may form coaggregates (Reynolds et al, 2011;Hellstrand et al, 2013b;van Maarschalkerweerd et al, 2014;Galvagnion et al, 2019;Gaspar et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…In vivo, the fibril formation process occurs in a highly lipid-rich environment, and Lewy bodies are known to contain significant amounts of lipid (Shults, 2006;Stefanis, 2012;Araki et al, 2019;Fanning et al, 2020;Lashuel, 2020). These facts have motivated studies of αS-lipid interactions, involving both monomeric (Fusco et al, 2014;van Maarschalkerweerd et al, 2014;Fusco et al, 2016;Hannestad et al, 2020;Makasewicz et al, 2021), andfibrillar αS (van Rooijen et al, 2009;Hellstrand et al, 2013b;Galvagnion et al, 2019;Gaspar et al, 2021). It has been shown that monomeric αS adsorbs to anionic lipid membranes (Jao et al, 2004;Pfefferkorn et al, 2012;Hellstrand et al, 2013a;Fusco et al, 2014), and that the membrane under some conditions can have a catalytic effect on fibril formation (Galvagnion et al, 2015;Grey et al, 2015;Galvagnion, 2017;Gaspar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%